2006
DOI: 10.1007/s11255-005-8440-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Pain and Infective Complications after Transrectal Prostate Biopsy: A Prospective Study

Abstract: Lavage with betadine prior to transrectal prostate biopsy is adequate in the prevention of infective complications; however, because lidocaine gel is not effective against pain, alternative methods for pain management need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our study did not explore on why patients were given antibiotics uphazardly but probably clinicians’ thoughts are to decrease of post intervention bacteriuria, or decrease of symptomatic UTIs or other infectious complications’ While the aim of preventing symptomatic UTIs and other serious infectious complications seems evident, the need to prevent asymptomatic bacteriuria remains questionable. Asymptomatic bacteriuria is often of no clinical importance and resolves spontaneously in many cases as the findings of other studies elsewhere [ 1 , 3 11 , 13 , 18 ]. This being a retrospective study, we could not asses the outcomes of those patients post urological intervention therefore we could not find high evidence supporting the use of antibiotic prophylaxis in urologic interventions to prevent complications such as UTI including in those who had TURP done as it was found out in other studies that no enough evidence supports the systematic use of antibiotic prophylaxis to prevent UTIs in the rest of the procedures.…”
Section: Discussionmentioning
confidence: 61%
“…Our study did not explore on why patients were given antibiotics uphazardly but probably clinicians’ thoughts are to decrease of post intervention bacteriuria, or decrease of symptomatic UTIs or other infectious complications’ While the aim of preventing symptomatic UTIs and other serious infectious complications seems evident, the need to prevent asymptomatic bacteriuria remains questionable. Asymptomatic bacteriuria is often of no clinical importance and resolves spontaneously in many cases as the findings of other studies elsewhere [ 1 , 3 11 , 13 , 18 ]. This being a retrospective study, we could not asses the outcomes of those patients post urological intervention therefore we could not find high evidence supporting the use of antibiotic prophylaxis in urologic interventions to prevent complications such as UTI including in those who had TURP done as it was found out in other studies that no enough evidence supports the systematic use of antibiotic prophylaxis to prevent UTIs in the rest of the procedures.…”
Section: Discussionmentioning
confidence: 61%
“…As previous cleansing with povidone-iodine has been reported to increase distress and irritation, this study demonstrates that the application of suppository types is effective in significantly lessening patient discomfort. [15]…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al [30] reported that rectal preparation with povidone-iodine is a safe and reliable method to prevent infections. Akay et al [31] reported lavage with povidone-iodine decreased the postbiopsy infection rates. Huang et al [32] combined povidone-iodine with a phosphate-based enema and found that postbiopsy infection rates were decreased significantly.…”
Section: Discussionmentioning
confidence: 99%